Analyse De La Contribution Des Collectivités Territoriales Au Développement Local En Côte D’ivoire : Cas Du Département D’agboville - N’tchuvi Tanoh Yves-Cyrille; Aloko-N’guessan Jérôme (European Scientific Journal, ESJ, 2018)
This study focuses on the contribution of local authorities to the development of the Agboville department. It allows the two (02) levels of communities involved in the planning and development of that department. These are the former general counsel of Agboville and the regional council of Agneby-Tiassa. The first was involved in the planning and development department said 2002 to 2012. The second takes over from 2013. The main objective of this study is to highlight the ability of these local entities to provide basic services to the population for their well-being. The methodological approach was to assess the triennial programs and administrative accounts of local authorities and conducting field surveys, to conduct interviews with local authorities and direct observation of the actions carried. The results show that investments by local authorities are poor. This deficiency is linked to the lack of financial resources, which therefore does not allow them to ensure adequate local development.